Christopher Harker, Spacing Debt: Obligations, Violence, and Endurance in Ramallah, Palestine, Durham: Duke University Press, 2021. ISBN: 9781478010968 (paper); ISBN: 9781478009900 (cloth); ISBN: 9781478012474 (ebook) - Green, W Nathan (Wiley-Blackwell, 2021)
ANTIPODE